Comparison of post ablation left atrial volume index versus left atrial reverse remodeling for prognostic events in persistent atrial fibrillation - Hironori Ishiguchi; Yasuhiro Yoshiga; Masakazu Fukuda; Shohei Fuji; Masahiro Hisaoka; Shintaro Hashimoto; Takuya Omuro; Noriko Fukue; Shigeki Kobayashi; Motoaki Sano (Scientific Reports)
Abstract Post-catheter-ablation left atrial volume index (LAVI) and left atrial reverse remodeling (LARR) predict successful sinus rhythm maintenance in patients with atrial fibrillation (AF). Although the prognostic value of LAVI has been established in prior literature, few have directly compared the clinical significance of LAVI and LARR. This study compared the significance of the post-ablation LAVI and LARR for clinical events after catheter ablation in patients (n = 365; age 66 ± 9 years; men, 77%) with persistent AF who underwent their first catheter ablation. We calculated the LARR magnitude using the pre- and post-ablation LAVI. Post-ablation LAVI and LARR were divided into tertiles and compared the incidence of major adverse cardiovascular events (MACE: all-cause death, unplanned heart failure hospitalization, and cardiovascular hospitalization) across tertiles. Over a median follow-up of 5.2 (interquartile range 3.1–7.0) years, 57 (16%) patients experienced at least one event. MACE incidence significantly increased across ascending post-ablation LAVI tertiles (cumulative incidence [95% confidence interval]: 1st [:<38 mL/m2], 8.4% [2.9–13.5] vs. 2nd [38–52 mL/m2], 11.6% [5.4–17.5] vs. 3rd [> 52 mL/m2], 21.7% [12.4–30.0], p < 0.001). However, MACE incidence was comparable across LARR tertiles (p = 0.900). Multivariate analysis identified post-ablation LAVI as an independent factor associated with post-ablation MACEs but not with post-ablation LARR. To conclude, the incidence of MACE increased significantly with the increase in post-ablation LAVI, but not with post-ablation LARR.